Analysis of Learning Methods of Students with Achievements and Students with Grades Below the KKM - Sri Ramadhani; Zainuddin Zainuddin; Nasrun Nasrun (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
Differences in student learning styles as part of individual characteristics that cause differences in student learning outcomes need to be considered in the learning process. This study aims to analyze the differences in the learning styles of high achieving students and students with scores below the KKM. This research is a qualitative research with a sample of 50 students of SMA Negeri 1 Aek Natas. Data collection techniques were carried out by giving questionnaires, interviews, and observation. Data analysis techniques were carried out using the Miles and Huberman methods. The results showed that for a visual learning style tendency of 28, students with a kinesthetic learning style tendency of 14, and students with an auditory learning tendency of 8. The learning style of achieving students with ratings 1-3 dominates the auditory where students prefer discussion and active in giving opinions to friends and teachers. The learning styles of students with grades below the KKM are all three. However, students prefer kinesthetic learning styles because the material is delivered practically so that students are more enthusiastic in learning activities.